Formulation, Evaluation Of Combination Of Rabeprazole And Baclofen Bilayer Tablet For The Treatment Of Gastroesophageal Reflux Disease (Gerd) - Shamim, Muddassir; Thagele, Rajkumari; Gupta, Mahesh Kumar; Singh, Ajay (Journal of Neonatal Surgery, 2025)
Gastroesophageal Reflux Disease (GERD) is a chronic condition characterized by the reflux of gastric contents into the esophagus, often requiring both acid suppression and control of lower esophageal sphincter relaxation. The present study focuses on the formulation and evaluation of a bilayer tablet containing Rabeprazole in the immediate-release layer and Baclofen in the sustained-release layer to provide dual-phase therapeutic action. Rabeprazole offers rapid proton pump inhibition, while Baclofen, a GABA-B agonist, reduces reflux episodes by decreasing transient lower esophageal sphincter relaxations. The bilayer tablets were formulated using appropriate polymers and excipients, optimized through preformulation studies, and evaluated for weight variation, hardness, friability, drug content, disintegration time, and in-vitro drug release. Results showed satisfactory physicochemical properties, effective separation of release profiles, and promising sustained action. The bilayer design significantly enhances patient compliance by combining two therapeutic approaches into a single dosage form, offering potential for improved clinical outcomes in GERD management